Ñipal F2016: variety of bread wheat for the Rural District 014 - Alvarado-Padilla, Jorge I.; Chávez-Villalba, Gabriela; Camacho-Casas, Miguel A.; Huerta-Espino, Julio; Villaseñor-Mir, Héctor E.; Singh, Ravi P. (Revista Mexicana de Ciencias Agrícolas, 2018)
Recent efforts in the Experimental Field of Mexicali Valley of the National Institute of Agricultural and Livestock Forestry Research have allowed the development of wheat varieties of high yield and industrial quality. Among these superior genotypes is the new bread wheat variety Ñipal F2016, which exceeds the yield of Cachanilla F2000 with 8.1%. It is also resistant to yellow linear rust, resistant to leaf rust, septoria, spica blight and shows good industrial quality. The seed of Ñipal F2016 is available in the Experimental Valley of Mexicali.
Keywords: Performance; quality; yellow rust